P75 Prognostic Implications Of The Modified Glasgow Prognostic Score In Early Stage Non-small Cell Lung Cancer. (10th November 2014) - MacKenzie, AM; Johnson, E; Tsim, S; Blyth, KG
Abstract : Introduction and objectives: Up to 50% of patients treated radically for non-small cell lung cancer (NSCLC) subsequently present with metastatic disease. This is despite rigorous case-selection and the use of adjuvant therapies based on clinical and/or surgical staging. A simple, objective biomarker that identified patients at higher risk of recurrence might facilitate more effective multi-modality radical treatment. Since inflammation-based biomarkers offer robust prognostication in metastatic NSCLC, we hypothesised that the modified Glasgow Prognostic Score (mGPS), Neutrophil:Lymphocyte Ratio (NLR) and/or Platelet:Lymphocyte Ratio (PLR), measured prior to radical treatment would have utility in this regard. Methods: Utilising a radiology database, we retrospectively identified all patients with Stage I-IIIa NSCLC who underwent radical treatment between August 2011 and August 2012. Electronic records were reviewed and baseline parameters, including blood results were recorded. mGPS (based on CRP and Albumin), NLR and PLR were calculated. All cases were subject to multidisciplinary assessment, detailed staging and 2-year follow-up. Kaplan-Meier plots were generated for mGPS, NLR, PLR and compared using log-rank for trend and log rank. Differences in mortality were quantified using Hazard Ratios (HR). Differences in stage proportion were compared using the Chi-Square z test. Results: 97 patients were identified. 44/97 (45%) were male, mean age 70 (± 8) years. 54/97 (56%) underwent surgery, 43/97 (44%) underwent radical RT. NLR and PLR provided no useful prognostic information. In surgical patients only, increasing mGPS was associated with decreasing 2-year survival (see Figure 1(a) ), with curve separation occurring 1 year post-resection. Pre-operative mGPS 1 and 2 were associated with HR for death of 3.9 (95% CI 0.8–39.5, p = 0.095) and 5.8 (95% CI 1.38–106, p = 0.02) relative to mGPS 0. There were less Stage I and more Stage II patients in the mGPS 1 group (see Figure 1(b) ), mGPS 0 and 2 appeared well matched for stage. Conclusion: These data suggest that pre-operative mGPS may be useful in risk-stratifying patients with early stage NSCLC. The late survival curve separation observed suggests recurrent malignancy rather than post-operative complications are likely to explain this. If confirmed prospectively, integration of mGPS into staging algorithms might allow more effective targeting of adjuvant therapies.